The act of playing within the hospital context in the vision of the accompanying persons of the hospitalised children - e Sousa, Lyana Carvalho; De Vitta, Alberto; de Lima, José Milton [UNESP]; De Vitta, Fabiana Cristina Frigieri [UNESP] (Faculdade de Filosofia e Ciências, 2015)
Introduction: the infant hospitalisation may put at risk the normal development of the children due to the breaking of their routine and the adjustment to the new reality process. There are several initiatives to promote spaces in hospitals so that the children can have contact with recreational activities. There are many variables that may influence the children’s attitude towards the possibility of playful activities, among them the involvement of the accompanying persons. It is essential to learn their interpretation of the playing activities in the hospital context and which characteristics are associated with this activity in order to reach better planning of the assistance. Objective: this study aimed to examine the opinion of the accompanying persons on promoting play during the children’s hospitalisation. Methods: therefore, the accompanying persons answered questionnaires during that period of hospitalisation. Data were analysed using descriptive statistics and content analysis. Results: 65 mothers of hospitalised children, mostly accompanied patients aged from 2-6 years old. All of them confirmed that the children should attend the playroom since it helps in recovery, providing relief from suffering, calming them and thus relieving tensions. Conclusion: as a conclusion, the accompanying persons highlight the importance of the playroom in the context of hospitalisation of children to soothe its effects of and help in the development of the children.
Keywords: accompanying persons; acompanhantes; brincar; hospital; play